2001
DOI: 10.1093/ndt/16.5.1042
|View full text |Cite
|
Sign up to set email alerts
|

Screening for renal disease using serum creatinine: who are we missing?

Abstract: This study documents the substantial prevalence of significantly abnormal renal function among patients identified by laboratories as having normal-range SCR: Including calculated estimates of GFR in routine laboratory reporting may help to facilitate the early identification of patients with renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
0
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(148 citation statements)
references
References 16 publications
11
128
0
9
Order By: Relevance
“…SCr concentration is the most widely used method of assessing renal function; however, in the present study SCr concentration method misplaced (108) 11.6% patients with impaired function. Our study is in harmony with Duncan et al [8] study reported that (13.9%) patients had misplaced with SCr concentration method. Yet another Indian study also forwarded similar results [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SCr concentration is the most widely used method of assessing renal function; however, in the present study SCr concentration method misplaced (108) 11.6% patients with impaired function. Our study is in harmony with Duncan et al [8] study reported that (13.9%) patients had misplaced with SCr concentration method. Yet another Indian study also forwarded similar results [11].…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that SCr alone may not be well correlated with true GFR [7], many clinicians continue to rely solely on SCr as a measure of renal function and interpret a normal SCr as indicating normal renal function. However, many patients with impaired kidney function are failing to notice when relying on SCr alone [8]. But how many patients with impaired kidney function are missed when relying on SCr alone?…”
Section: Introductionmentioning
confidence: 99%
“…GFR in the 30-to 80-ml/min range in older people is often accompanied by a serum creatinine within the laboratory normal range (37,41) and may go unrecognized, uninvestigated, and unreferred (41). Only a minority of patients with an elevated creatinine are referred to nephrologists (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Band et al 23 reported that creatinine clearance in 40% of patients was lower than 60 mL/min, despite a serum creatinine level of 1.5 mg/dL or lower. Similarly, Duncan et al 24 noted that creatinine clearance in more than 15% of patients was lower than 50 mL/min when they had normal serum creatinine levels. In our study, the creatinine clearance of 23 (44%) of 52 patients with creatinine levels of 1.5 mg/dL and lower was lower than 60 mL/ min.…”
Section: Discussionmentioning
confidence: 89%
“…In the (20)(21)(22)(23)(24)(25)(26)(27) 0.56 dBP = diastolic blood pressure; RR = respiratory rate; sBP = systolic blood pressure; NAC = N-acetylcysteine. Data are reported as n (%) unless otherwise noted.…”
Section: Discussionmentioning
confidence: 99%